Experiment Tests and Numerical Simulations of Leakage from Double-Hull Oil Tanks in a Fixed State - Wenzhuo Zhang; Renqing Zhu; Xinlong Zhang; Qingyi Qu; Hui Zhao (Journal of Marine Science and Engineering, 2026)
To investigate the leakage characteristics of damaged double-hull oil tanks in still water, this study conducted both model tests and numerical simulations on the leakage process of a damaged double-hull oil tank model. Based on a 75,000 DWT oil tanker, a scaled model was designed according to similarity criteria. The effects of different damaged locations (side-shell and bottom) and various breach sizes on the tank’s leakage behavior were examined. The evolution of multiphase flow inside the tank and the surrounding flow field was captured, and the leakage pressure under fixed model conditions was measured. The model test results indicate that larger breach sizes lead to a more rapid stabilization of the pressure load during leakage and the liquid exchange process. For side shell breaches, after an initial phase of pressure-difference-driven leakage, a density-driven flow develops at the stable liquid interface. Bottom breaches cause flooding that results in an oil sealing phenomenon at the bottom, leading to a pronounced oil–water stratification. Corresponding numerical simulations of the model tests were performed, and the results were compared and validated against the model test data.